The Scandalous Lord Lanchester - Herries, Anne (Harlequin (UK) Limited, 2012)
THE WAYWARD WIDOW With her wealth, beauty and playful nature, young widow Mariah Fanshawe is not short of suitors. Yet the only man she wants to marry is immune to her obvious charms! Upright Andrew, Lord Lanchester has always seemed determined to resist, but Mariah has a new plan to win him over... Andrew is thrown when Mariah asks him to help her find a husband. The truth is he$1 (Bd like nothing more than to make the wild Mariah his own obedient wife! But Andrew is living in the shadow of a scandal... SECRETS AND SCANDALS Nothing stays secret for long in Regency Societys
Keywords: Romance-Fiction